Role of Ferroptosis in ALD: Focusing on Hepcidin and Besides Hepcidin - Chen, Leijie; Zhou, Hejun; Cheng, Zongyong; Liu, Deliang; Tan, Yuyong (Current Medicinal Chemistry, 2025)
Ascending incidence and poor outcomes make Alcoholic Liver Disease (ALD) a considerable public health concern. This review concluded the iron metabolism under physiology conditions and alcohol disturbance (leading to ferroptosis in ALD) and summarized the novel treatment, diagnosis, and prognosis of ferroptosis for ALD. ALD is characterized by alcohol-induced chronic metabolism disorder, peroxidation damage, and dysfunction of the anti-oxidant system. Current animal experiments and clinical studies identified ferroptosis as a new form of regulated cell death involved in ALD. One strong evidence is that the key iron regulatory hormone, hepcidin, is downgraded in ALD through NF-κB/IL-6/STAT3, BMP/SMAD, and Jak/STAT3 pathways, which would impair iron hemostasis and induce ferroptosis in ALD. Also, imbalance metabolism and other pathological responses in ALD induce and regulate ferroptosis, which proves ferroptosis participates in the pathophysiology of ALD via oxidative stress, steatosis, and fibrosis. Inhibition of ferroptosis via regulating hepcidin expression and metabolism impairment may provide new therapies for ALD.
Keywords: iron metabolism